Higher Education Systems and the Tuition Fees Charging: Perspectives and Perceptions n Brazil, Canada and China - Costa, Danilo de Melo (2019)
This study aims to understand the perceptions of the tuition fees charging in Canada and China and the perspectives of this practice in Brazil, which is a country where society requires access to quality higher education, but which faces large budgetary constraints on its public funding. To understand these questions, a qualitative exploratory multi-case study was carried out with government officials, specialists in higher education, and student leadership from all three countries. In conclusion to this analysis, and considering the benefits provided by the Canadian and Chinese participants, it is suggested for Brazil to perform a reflection on this subject. The study shows that such an initiative can boost public higher education institutions through greater financial availability and democratize access and permanence, as there would be more resources to invest and assist students from underrepresented groups participating in the system.